The Existence of Fixed Points for γ-FG-contractive Condition via Cyclic (α,β)-admissible Mappings in b-metric Like Spaces - Sudip Kumar; G. V. V. Jagannadha Rao; P. Sudheer Kumar (International Journal of Mathematics And its Applications, 2024)
This paper extends and generalizes the results of paper Padhan [14]. We show various fixed point theorems for such mappings in a complete b-metric like space, and propose the novel ideas of cyclic (α,β)-admissible mapping utilising γ-FG-contractive mapping. Adequate illustrations are provided to validate the findings, along with the implications of the primary findings.